The Construction of Personal Identity through Internalizing Societal Norms - Bendouma Noureddine (UATL, 2018)
The problem of personal identity baffled many writers and philosophers throughout history. The answer to such a problem is not as simple as it may look. The difficulty in answering the types of questions which are resulted from the problem does not lie in the lack of answers, but in the fact that there are no fixed criteria in answering them. This lack of consensus committed the philosophers’ and thinkers’ endeavors to scaffold on the endless mountain to reach the truth, which is beyond. The problem of personal identity attempt to examine the very nature of human beings, by means of trying to find out what features help recognize a person as who he is, apart of the common features which all human beings share.
Case Study: The Protagonist in Kurt Vonnegut’s The Sirens of Titan
Thesis Nouveau pole, bra
Keywords: Computer Science